SEJARAH, METODE DAN IJTIHAD HUKUM ISLAM PADA MASA NABI MUHAMMAD SAW - Muhazzir Budiman (STIS Nahdlatul Ulama Aceh, 2020)
Scientists share several periods of the development of Islamic law from time to time. The periodization of Fiqh is divided into 6, namely; Minutes period, khulafaurrasyidin period, fiqh growth period, golden period, period of review and debate, and period of decline. However, the main focus of this article is tasyri 'in the period of the Prophet. There are three formulations of the problem in this research, namely: How is the history of the development of Islamic law during the period of the Prophet? What was the method of establishing Islamic Law during the Prophet's period? Did the Prophet have ijtihad ?. The purpose of this research is to find out the history of the development of Islamic law during the Prophet's period, to find out what the method of establishing Islamic law in the Prophet's period was, to find out whether the Prophet had ijtihad. The research method used was the library research method. By using normative and socio-historical approaches. The results showed that the history of the development of Islamic law during the Prophet's period was twofold, namely the Mecca period, namely before the Prophet's migration to Medina. The Medina period, which is after the Messenger of Allah moved to Medina. Meanwhile, there are three methods of determining Islamic law at the time of the Prophet, namely gradual, making laws more efficient and providing convenience and relief. As for the Prophet's ijtihad, there are two groups of opinion: the Asy'ariyah group and the majority of the Mu'tazilah saying there is no Prophet's ijtihad. The majority of ushul scholars say there is the Prophet's ijtihad.